2000
DOI: 10.1152/jn.2000.83.5.2854
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Bötzinger Complex Functions as a Central Hypoxia Chemosensor for Respiration In Vivo

Abstract: Recently, we identified a region located in the pre-Bötzinger complex (pre-BötC; the proposed locus of respiratory rhythm generation) in which activation of ionotropic excitatory amino acid receptors using DL-homocysteic acid (DLH) elicits a variety of excitatory responses in the phrenic neurogram, ranging from tonic firing to a rapid series of high-amplitude, rapid rate of rise, short-duration inspiratory bursts that are indistinguishable from gasps produced by severe systemic hypoxia. Therefore we hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 60 publications
1
104
0
1
Order By: Relevance
“…At these two ages, and especially at P12, reduced CO activity suggests a transient adjustment in synaptic activity of the PBC, possibly involving decreased excitatory drive and/or enhanced inhibitory drive. The PBC, being the presumed center of respiratory rhythm generation (42) and a central hypoxia chemosensor for respiration (44), may be less responsive to abnormal respiratory demands during these periods of low CO. Consequently, the system may be more vulnerable to failure when stressed by insults such as ischemia, hypoxia, and other respiratory distress. Changes in CO activity and neurochemical immunoreactivity at P3-P4 and P12 occur despite a steady increase in neuronal size with age, indicating that they are not related to cell growth per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At these two ages, and especially at P12, reduced CO activity suggests a transient adjustment in synaptic activity of the PBC, possibly involving decreased excitatory drive and/or enhanced inhibitory drive. The PBC, being the presumed center of respiratory rhythm generation (42) and a central hypoxia chemosensor for respiration (44), may be less responsive to abnormal respiratory demands during these periods of low CO. Consequently, the system may be more vulnerable to failure when stressed by insults such as ischemia, hypoxia, and other respiratory distress. Changes in CO activity and neurochemical immunoreactivity at P3-P4 and P12 occur despite a steady increase in neuronal size with age, indicating that they are not related to cell growth per se.…”
Section: Discussionmentioning
confidence: 99%
“…All six basic types of respiratory neurons were identified in the PBC (9, 42), and neurons with voltagedependent pacemaker-like properties were also found there (6,7,17,22,47). It has been implied that the PBC functions as a central hypoxia chemosensor for respiration (44,45). The application of agonists and antagonists of some neurotransmitters and neuromodulators to the PBC can induce apparent changes in respiratory rhythm and pattern (8,21,34,41,43).…”
mentioning
confidence: 99%
“…The preBötzinger complex (preBötC) in the ventral medulla is critical for respiratory rhythm generation (25,26) and may play a role in the hypoxic response (27,28). Extracellular recordings of brain stem slices containing the preBötC were obtained from P8-P10 KO mice and their control littermates.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue we recorded from the pre-Bötzinger complex (preBötC) and characterized its response to graded reductions in O 2 . The preBötC is a neuronal network involved in respiratory rhythmogenesis during both well-oxygenated and hypoxic conditions (Peña 2008;Solomon et al 2000). Previous studies of the isolated brain stem slice [postnatal day zero (P0) to P18] have shown that exposure to very low levels of O 2 (i.e., 0% O 2 or hypoxia) affects both the frequency of the in vitro respiratory rhythm (Ramirez 1997a(Ramirez , 1998Telgkamp and Ramirez 1999) and the waveform of the extracellularly recorded population bursts (Lieske et al 2000).…”
Section: Introductionmentioning
confidence: 99%